Peran AirAsia Mendukung Terwujudnya Integrasi ASEAN 2015 - Uswatun Hasanah (HI 15 UMY 399, 2015)
*399 This paper aims to analyze the role of AirAsia to support the realization of ASEAN integration 2015. AirAsia is one of the well-known multinational corporation in ASEAN. In the AirAsia’s business track record during 14 years, from 2001 to 2015, AirAsia has fulfilled AirAsia as a low cost airlines company makes the connectivity of ASEAN nations in its efforts to support ASEAN integration 2015 with many ways, from efficiency measures until make integration as its business branding. AirAsia targeted to be the major low cost carrier in the ASEAN region and become the most ready airlines in ASEAN Economic Community